Pengaruh Implementasi SPIP terhadap Penatausahaan Aset Tetap serta Implikasinya pada Kualitas Laporan Keuangan - Alya Dhiya Fauzan; Iyeh Supriatna; Hastuti (Indonesian Accounting Research Journal, 2021)
There are still many shortcomings in the administration of fixed assets in the West Bandung Regency Government. This will have an impact on the financial reports it produces. Therefore, supporting factors are needed so that the administration of fixed assets can run well and in accordance with applicable regulations, a Government Internal Control System (SPIP) is needed. SPIP aims to provide adequate assurance for the achievement of organizational goals through effective and efficient activities, reliability of financial reporting, safeguarding state assets, and compliance with laws and regulations. The purpose of this study was to examine the effect of SPIP on fixed asset administration and its implications for the quality of financial Reports. The population in this study were all SKPD in the West Bandung Regency Government with a sample of 28 SKPD. Sources of data used are primary data obtained directly from the results of distributing questionnaires. The research method used is survey research with a quantitative descriptive approach. The analytical method used is path analysis and Sobel test. The results showed that directly, SPIP had a positive and significant effect on the administration of fixed assets, the administration of fixed assets had a positive and significant effect on the quality of financial reports, SPIP had a positive and significant effect on the quality of financial reports. Indirectly, SPIP has a positive and significant effect on the quality of financial reports through the administration of fixed assets.